Micro embossing of graphite-based anodes for lithium-ion batteries to improve cell performance. (15th August 2023) - Sandherr, Jens; Kleefoot, Max-Jonathan; Nester, Sara; Weisenberger, Christian; DeSilva, Anjali K.M.; Michel, Dominik; Reeb, Sarah; Fingerle, Mathias; Riegel, Harald; Knoblauch, Volker
Abstract: Patterning of lithium-ion battery anodes is widely accepted as a method to overcome the lack of fast-charging capability of high-energy electrodes. Structuring is mostly performed by ablative laser processes, whereby technological aspects such as loss of active material and scalability are still an obstacle to industrial implementation. In this paper, micro embossing is proposed as a novel material-preserving approach for graphite-based anodes to improve their performance. A metal stamp with well-defined laser-structured micro pins was developed first. Subsequently, a lab scale process was developed to imprint a defined perforation pattern on calendered graphite anodes. The electrochemical performance is compared to reference electrodes prior to any post-treatment. By micro embossing, hole geometries could be achieved compared to laser perforation known from the literature. Microscopy and tomography investigations of the embossed hole surface wall show lower porosity as well as alignment of graphite particles. Electrochemical impedance spectroscopy of symmetrical anode cells indicates a reduction in the ionic pore resistance of the embossed anodes. Moreover, fast-charging tests with full-cells revealed reduced cell overpotentials compared to pristine anodes. A cell test over 400 cycles showed improved retention of capacity of the embossed anodes compared to reference anodes. Half-cell capacity tests confirmed that there is practically no loss of active material due to micro embossing. Regarding the layer adhesion, no disadvantage could be found either. Moreover, this process has the potential to be integrated comparatively easily into electrode production, if it can be combined with the calendering process, thus, enhancing its industrial applicability. Graphical abstract: Unlabelled Image Highlights: A stamp with defined pins was designed to emboss a hole pattern in graphite anodes. In doing so, the ionic pore resistance of the anodes can be reduced significantly. Cell tests show decreased overpotentials and enhanced fast-charging capability. There is no active material loss and the result appears similar to laser processing. However, local compaction and alignment of particles on the hole wall is observed